LMIs in control systems : analysis, design and applications - Duan, Guangren, 1962-; Yu, Hai-Hua (CRC Press, Taylor & Francis Group, 2013)
"Preface In recent years linear matrix inequalities (LMIs) have emerged as a powerful tool in the field of control systems analysis and design. Many problems such as state feedback synthesis, robustness analysis and design, H2 and H? control, can all be reduced to convex or quasi-convex problems that involve LMIs. The most attractive feature of LMIs lies in the fact that many problems in systems and control can be reduced to LMI problems, which can be solved both efficiently and numerical reliably. Very efficient algorithms to solve linear matrix inequalities have been developed and can be readily used through the mature Matlab LMI toolbox or the open source software packages YALMIP and CVX. LMIs today has been a real technique. With the help of the LMI techniques in control systems analysis and design, more and more theoretical and practical applications can now be solved, many of which might not be otherwise solved by traditional methods. Goal of the book The goal of this book is to provide a textbook for graduate and senior undergraduate courses in the field of control systems analysis and design, which contains the basic but systematic knowledge about LMIs and LMI-based control systems analysis and design. Boyd et al. (1994), which is the first book on LMIs, certainly has performed a pioneering function in the field, but limited by time it fails to catch up with the ever fast emerging new theories and techniques in LMIs. Yu (2002) is a book on LMI approach to robust control, which is suitable to be used as a textbook, but the Chinese language limits its usage worldwide"--Resumé vydavatele
Keywords: teorie řízení; teorie matic; matematická optimalizace; řídicí systémy; control theory; matrix theory; mathematical optimization; control systems; učebnice vysokých škol; textbooks (higher)